The synthesis and evaluation of new benzophenone derivatives as tubulin polymerization inhibitors. Issue 91 (16th September 2016) - Zhang, Shun; An, Baijiao; Yan, Jun; Huang, Ling; Li, Xingshu
Abstract : Inspired by the potent inhibition activity of phenstatin and millepachine against cancer cell growth, a series of new benzophenone derivatives were synthesized and evaluated as tubulin polymerization inhibitors. Abstract : Inspired by the potent inhibition activity of phenstatin and millepachine against cancer cell growth, a series of new benzophenone derivatives were synthesized and evaluated as tubulin polymerization inhibitors. Among them, compound10a exhibited 0.029–0.062 μM of IC50 for five human cancer cell lines, which is much better than that of the two leading compounds. Flow cytometric analysis showed that10a induces G2/M phase arrest and apoptosis in A549 cells. Cellular studies revealed that the induction of apoptosis by10a was associated with the collapse of the mitochondrial membrane potential (MMP). Overall, the current study demonstrates that the benzophenone derivatives are promising anticancer agents by targeting tubulin.